Interactive effects of temperature and velocity on the feeding behavior of competing native and invasive stream fishes - Kindree, Meagan M.; Jones, Nicholas E.; Mandrak, Nicholas E. (Frontiers in Ecology and Evolution, 2024)
The integration of invasive species into native communities may result in the destabilization of food webs through predation of native prey and competition with native predators. These negative effects are likely to be exacerbated by climate change, increasing the frequency of heat waves, droughts, and high-flow events. Invasive Round Goby (Neogobius melanostomus) and native White Sucker (Catostomus commersonii) collected from the wild and acclimated to a range of temperatures expected to capture increases in temperature under climate change. In the laboratory, we measured the effects of temperature (19, 22, 25, and 28⁰C) and velocity gradients (0. 0.15, 0.3, 0.6 m/s at 22 and 25⁰C) on the prey consumption and foraging behaviour of each species. We found that the prey consumption and number of attacks (lunges at prey) of both species increased with temperature but were consistently higher in Round Goby. Velocity had an interactive effect with temperature for prey consumption and foraging behaviour, where generally, velocity tolerance for both species was higher at 22⁰C than at 25⁰C. White Sucker tolerance to velocity was higher than Round Goby, suggesting that systems with higher velocities may have a competitive advantage in high-flow environments. Our results stress the importance of interactive experiments when examining the impact of invasive species on native competitors under shifting climatic conditions.